Art as a pathway to God. A historical-theological study of the Jesuit mission to China, 1552-1773. By Susangeline Yalili Patrick. (Theology and Mission in World Christianity, 28.) Pp. xii + 264 incl. 48 colour ills and 3 colour maps. Leiden-Boston: Brill, 2024. € 59 (paper). 978 90 04 67771 5; 2452 2953 - Vermote, Frederik (The journal of ecclesiastical history, 2025)
Art as a pathway to God. A historical-theological study of the Jesuit mission to China, 1552-1773. By Susangeline Yalili Patrick. (Theology and Mission in World Christianity, 28.) Pp. xii + 264 incl. 48 colour ills and 3 colour maps. Leiden-Boston: Brill, 2024. € 59 (paper). 978 90 04 67771 5; 2452 2953 - Volume 76 Issue 3